Low dose-extended letrozole versus double dose-short letrozole protocol for ovulation induction in polycystic ovary syndrome - Jahan, Shirin; Deeba, Farzana; Ishrat, Shakeela; Banu, Jesmine; Rani, Chalontika; Akter, Sumaiya; Nazneen, Sohely; Jahan, Nishat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Letrozole, an aromatase inhibitor has been regarded as the first line drug for ovulation induction in anovulatory PCOS patients because of its monofollicular growth and there is no chance of hyperstimulation by letrozole. Traditional protocol of letrozole includes administration of letrozole for 5 days in first half of follicular phase which induces ovulation in 61.7% cases. Few recent studies have shown that extended letrozole protocol causes more follicles to grow and induces more ovulation than the traditional protocol. The aim was to compare the effects of low dose-extended letrozole protocol and double dose-short letrozole protocol for ovulation induction in infertile PCOS patients. Methods: A randomized controlled trial (RCT) was conducted in the department of reproductive endocrinology and Infertility at Bangabandhu Sheikh Mujib Medical University (BSMMU) on seventy infertile polycystic ovary syndrome patients. Low dose-extended letrozole group or experimental group received tablet letrozole 2.5 mg daily for 10 days and double dose-short letrozole group or control group received tab. Letrozole 5 mg daily for 5 days starting from the 2nd day of menstrual cycle or withdrawal bleeding. The ovarian response was assessed by folliculometry on day 12 of menstrual cycle by transvaginal sonography for measurement of total number of growing follicles, biggest follicle size and endometrial thickness. Mid luteal serum progesterone was measured on day 21-23 to confirm ovulation. Results: The mean number of growing follicle was 1.44±0.95 versus 0.99±0.65 in low dose-extended letrozole group and double dose-short letrozole group respectively generating p value of 0.001. The mean size of the dominant follicle at day 12 was greater in low dose-extended letrozole group than the other displaying 17.69±3.63 mm and 16.6±3.49 mm respectively but the difference was not statistically significant. The number of ovulating patients was greater in low dose-extended letrozole group (76.5% versus 71.9%), but without significant statistical difference. Pregnancy rate was insignificantly greater in low dose-extended letrozole group (23.5% versus 18.8%) as well. Conclusions: Low dose-extended letrozole protocol produces more multifollicular growth and larger size dominant follicle with a trend to raise the ovulation rate and pregnancy rate, though insignificantly.